GENETIC ASSESSMENT AND ESTIMATION OF COMBINING ABILITY FOR OIL AND YIELD RELATED TRAITS IN SUNFLOWER (HELIANTHUS ANNUUS L.) - SAEED, MQ; RAZZAQ, H; MUSTAFA, W; FAROOQI, MH; FATIMA, QUA; TANVEER, A; KISHWAR, S; SAWAR, MKS; ASGHAR, S; MAJEED, T (Biological and Clinical Sciences Research Journal, 2022)
Pakistan is inadequate in vegetable oil, and an enormous amount is spent on its import. This is due to the lack of local varieties of oilseed crops in the country. Sunflower (Helianthus annuus L.) is used as a supreme oilseed crop due to its higher oil content. Its hybrids are popular due to its cross-pollinated mode. The present study was conducted for the evaluation of crosses that were better in oil and yield-related traits. For this purpose, 8 parental genotypes were collected, including 5 female and 3 male parents. The subsequent Line × Tester breeding scheme crossed these parental genotypes. Fifteen crosses and eight parental lines were evaluated in Randomized Complete Block Design by using three repetitions. At maturity, data was collected for the following traits such as head diameter, time to bud formation, time to flower initiation, time to maturity, leaf area, plant height, no. of leaves per plant, no. of ray florets per head, 1000 achene weight, achene yield per plant, protein contents and oil contents. Crosses having better yield were selected. Among parents, lines 3-A, 11-A, and 23-A, while testers 79-R and 20-R were the best general combiners for head diameter, time to bud formation, time to flower initiation, time to maturity, leaf area, plant height, number of leaves/plants, 1000 achene weight, achene yield/plant and oil contents. SCA effects showed that cross combination of 12-A × 20-R, 11-A × 78-R, and 20-A × 79-R was best for time to bud formation, the number of leaves per plant, 1000 achene weight, plant height, time to flower initiation and oil contents, respectively. The information obtained from the hybrids can be used in further breeding programs.